(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2022)
OTT (over-the-top video streaming) services have revolutionized the way which consumers watch television. Understanding how video-on-demand (VoD) technology progresses and what consequences might be projected from the continued use of VoD is becoming more important for an information system’s long-term viability. The study is primarily concerned with whether or not current SVOD subscribers want to maintain using the service in the long run. Subscription video on demand (SVOD) is an over-the-the-top (OTT) service where users may access media content via a variety of innovative delivery methods made possible by advances in information and communication technology (ICT). An investigation into OTT services and video on demand (VoD), the OTT and VoD market in India, and the impact of covid-19 on OTT platforms are discussed in the study. User retention in Information Systems relies heavily on their ability to stay engaged with a product or service over time. Service providers and content creators alike are reaping the benefits of the growing popularity of over-the-top (OTT) streaming services.